2010
DOI: 10.1089/jpm.2009.0341
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Advance Care Planning for Community-Dwelling Elders

Abstract: Background: Advance planning for end-of-life care has gained acceptance, but actual end-of-life care is often incongruent with patients' previously stated goals. We assessed the flow of advance care planning information from patients to medical records in a community sample of older adults to better understand why advance care planning is not more successful. Methods: Our study used structured interview and medical record data from community-dwelling older patients in two previous studies: Assessing Care of Vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 17 publications
1
60
1
Order By: Relevance
“…In contrast to prior work among older adults at increased risk for death or functional decline, which demonstrated that pa- tient preferences for care are often not available within the medical record, 17 we found that most patients with stage IV cancer had had their preferences for care documented, although documentation appeared more often in clinician notes than in a formal AD. Many patients had more than one note describing their preferences documented in the medical record, with the first documentation of preferences appearing on average 2 months after diagnosis of advanced cancer and within 5 months of death.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to prior work among older adults at increased risk for death or functional decline, which demonstrated that pa- tient preferences for care are often not available within the medical record, 17 we found that most patients with stage IV cancer had had their preferences for care documented, although documentation appeared more often in clinician notes than in a formal AD. Many patients had more than one note describing their preferences documented in the medical record, with the first documentation of preferences appearing on average 2 months after diagnosis of advanced cancer and within 5 months of death.…”
Section: Discussioncontrasting
confidence: 99%
“…8 Similar findings among community-dwelling vulnerable elders were obtained in a secondary analysis of data from 2 related studies; only 15% to 47% of 800 elders who reported completing an advance directive and giving it to a health care clinician had corresponding documentation in the medical record. 9 Agreement between expressed and documented preferences may be affected by the fact that a substantial proportion of older adults completing advance directives may not fully understand these documents. 10,11 Advanced care documentation must be readily accessible to clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…9 Even when these discussions occur, a patient's wish might not be documented or followed through by other health care providers in a different health care setting. 8,10 The Physician Orders for Life-sustaining Treatment (POLST) form complements an advanced directive to ensure the patient's preferences about end-of-life care are followed in any health care setting. The purpose of this evidence-based education program was to increase progressive care unit (PCU) registered nurses' (RNs') knowledge and comfort levels using the POLST form.…”
Section: Introductionmentioning
confidence: 99%